2012
DOI: 10.4103/0019-557x.99902
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries and dental fluorosis among 12 and 15 years old school children in relation to fluoride concentration in drinking water in an endemic fluoride belt of Andhra Pradesh

Abstract: There was a negative correlation between dental caries and fluoride concentration for the entire study population. However, in high fluoride areas, there was a positive correlation between fluoride concentration and dental caries. Water defluoridation on an urgent basis is a priority here than water fluoridation, because the prevalence and severity of dental flurorosis is very high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 1 publication
1
23
1
5
Order By: Relevance
“…6,7 In Brazil, most cities have more than one water supply source and these sources have not yet been appropriately studied regarding fluorination levels. Therefore, population-based studies are required, especially considering that the population currently has access to various additional sources of fluoride, in particular fluoridated dentifrice.…”
mentioning
confidence: 99%
“…6,7 In Brazil, most cities have more than one water supply source and these sources have not yet been appropriately studied regarding fluorination levels. Therefore, population-based studies are required, especially considering that the population currently has access to various additional sources of fluoride, in particular fluoridated dentifrice.…”
mentioning
confidence: 99%
“…Indeed, recent epidemiological surveys reveal a high prevalence of enamel hypomineralization, even in areas where the concentration of fluoride in water was reduced. (20,21) In addition, the prevalence of DF in the US among adolescents aged 12-15 was higher in 1999-2004 than in 1986-1987. (22) This as of yet unexplained increased sensitivity to fluoride coincides with the increased incidence of several diseases cited above and the emergence of MIH.…”
Section: Introductionmentioning
confidence: 99%
“…This estimate in our study is very less as compared to other studies done in other states of India. A higher prevalence of 91.2% was reported from the Punjab, 10 61-66.7% from Birbhum, West Bengal 11 , 71% from Nalgonda in south 12 and 45.7% from Rajasthan. 13 The present study did not show severe fluorosis in any of the students and only 0.2% of students had moderate fluorosis.…”
Section: Discussionmentioning
confidence: 86%
“…14 On the contrary, another study conducted among children of Tamil Nadu and Nalgonda, prevalence was reported more among boys than girls. 12,15 Majority of the children were in intellectually average intelligence group (grade III: 83.3%). Higher proportion of boys belonged to intellectually above average and average intelligence group as compared to girls; however, the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%